1975
DOI: 10.3171/jns.1975.42.1.0101
|View full text |Cite
|
Sign up to set email alerts
|

Chronic subdural hematoma simulating transient cerebral ischemic attacks

Abstract: A patient is presented in whom chronic subdural hematoma simulated transient ischemic attacks. The neurological manifestations were those of recurrent, transient episodes of expressive dysphasia preceded by focal sensory deficit. Various pathophysiological mechanisms which could have caused the unusual clinical picture are briefly considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Aphasia was the most common symptom in our patients and occurred in 9 of 13 patients with CSH on the left side. Of previously reported patients, 1 1 of 13 with TNDs had aphasia {3, 4,11,13,14,17,IS]. Aphasia is therefore the most common symptom of TNDs associated with CSH.…”
Section: Discussionmentioning
confidence: 97%
“…Aphasia was the most common symptom in our patients and occurred in 9 of 13 patients with CSH on the left side. Of previously reported patients, 1 1 of 13 with TNDs had aphasia {3, 4,11,13,14,17,IS]. Aphasia is therefore the most common symptom of TNDs associated with CSH.…”
Section: Discussionmentioning
confidence: 97%
“…Transient focal neurological dysfunction has been reported with extracerebral masses with possible mechanisms including compression of vessels subjacent to the mass, postictal suppression, and spreading cortical depression after mechanical stimulation of cortex. 3 A transient increase in regional swelling might also cause a critical degree of vascular Fig. 1 e Right frontoparietal convexity meningioma lying over the parietal area and producing mass effect on underlying parietal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Ross thought that a focal seizure discharge would be a reasonable explanation for such attacks,6 but Melamed et al suggested that other mechanisms were more likely, including intermittent compression of surrounding vessels, spreading cortical depression of the type associated with migraine after mechanical stimulation of the cortex, and even coexistent thromboembolic transient ischaemic attack. 7 Moster et al noted that aphasia was the most frequent presenting symptom of these transient neurological deficits, though suggested that repeated small haemorrhages into the haematoma might be responsible. 8 The subsequent clinical course in our patient suggests that the episodes of loss of speech were the first manifestation of epilepsy.…”
Section: Discussionmentioning
confidence: 99%